A self-reported questionnaire for quantifying illness symptoms in elite athletes - Alexander Matthews; David Pyne; Philo Saunders; et al (Dove Medical Press, 2010)
Alexander Matthews1, David Pyne1,2, Philo Saunders2, Kieran Fallon1,2, Peter Fricker1,21Medical School, Australian National University, Canberra, ACT, Australia; 2Australian Institute of Sport, Canberra, ACT, AustraliaPurpose: To develop and evaluate a questionnaire that quantifies the self-reported frequency, duration and severity of illness symptoms in highly-trained athletes. We examined whether runners had more symptoms than recreationally-active individuals, and whether runners more prone to illness were undertaking more strenuous training programs.Methods: A daily illness questionnaire was administered for three months during the summer to quantify the type, frequency, duration, and severity of illness symptoms as well as the functional impact on the ability to undertake exercise performance. A total of 35 participants (12 highly-trained runners living in a community setting and 23 recreationally-active medical students) completed the questionnaire.Results: Runners had a similar frequency of illness (2.1 ± 1.2 vs. 1.8 ± 2.3 episodes, mean ± SD, P = 0.58), but substantially longer duration (5.5 ± 9.9 vs 2.8 ± 3.1 days, P < 0.01) and illness load (7.7 ± 16.2 vs 4.5 ± 4.8 units, P = 0.001) than age- and sex-matched recreationally-active individuals respectively. Runners more prone to illness symptoms had marginally higher training loads.Conclusions: The athlete illness questionnaire is useful for quantifying the pattern of self-reported symptoms of illness in field settings. Highly-trained runners experience longer episodes of illness with a greater impact on daily activity than recreationally-active individuals.Keywords: athlete, self-reported illness, questionnaire, exercise performance